Cover Picture: Organic Dye Adsorption by Amphiphilic Tris‐Urea Supramolecular Hydrogel (Chem. Asian J. 16/2017). Issue 16 (2nd August 2017) - Takeshita, Juri; Hasegawa, Yuki; Yanai, Kazushige; Yamamoto, Ayumu; Ishii, Ayumi; Hasegawa, Miki; Yamanaka, Masamichi
Abstract : Adsorption experiments of organic dyes were performed using supramolecular hydrogels of an amphiphilic tris‐urea derivative. Cationic organic dyes were adsorbed efficiently; indeed, the adsorption of methylene blue was as high as 4.19 mol equivalents relative to the gelator. Two luminescence peaks were observed in the rhodamine 6G‐adsorbed supramolecular hydrogels, and their ratios varied with the amount of dye adsorbed. The results suggest that the adsorption proceeded gradually, that is, occurring initially on the fibers and later in the aqueous spaces of the supramolecular hydrogels. More information can be found in the Communication by Miki Hasegawa, Masamichi Yamanaka et al. onpage 2029 in Issue 16, 2017 (DOI:10.1002/asia.201700708 ).